A Qualitative Inquiry into Rural Primary Schooler's Hygiene during the Covid-19 Pandemic in Kupang regency, East Nusa Tenggara Province, Indonesia - Nayoan, Christina Rony; Kiling, Indra Yohanes (Journal of Public Health for Tropical and Coastal Region, 2021)
Introduction: The importance of personal hygiene in preventing the spread of infection cannot be underestimated. Handwashing is an essential aspect of personal hygiene, especially among children. This study aimed to explore primary school students' hygiene in rural and remote areas in the Kupang regency. Methods: This study was conducted as a part of the end line evaluation of the MEMBACA II project. Teachers from four primary schools in three villages were purposively selected to participate in this study. The teachers were recruited from the participant schools of the MEMBACA II Project. Data was collected using phone interviews. Data were analyzed using inductive thematic analysis. Results: In total, there were 31 participants across four primary schools interviewed. The participants consisted of teachers, village leaders, village reading camp facilitators, and school supervisors. Participants were recruited as a proxy for providing information about students' hygiene. There were three themes identified as a result of the data analysis. The first theme is an improvement in children’s hygiene behavior. The second theme is the benefit of the little doctor program in children’s hygiene practices. The third theme challenges in children’s hygiene promotion and education. Overall, children were used to handwashing practices. They understood the importance of handwashing, especially during the Covid-19 pandemic. They were also aware of four essential times of handwashing. However, the adults perceived the need for handwashing equipment and access to clean water were the main challenges to maintaining students' hygiene. Conclusion: The study demonstrated the significance of regularly teaching children about handwashing in making handwashing habits among these youngsters. A continuing provision of health literacy and access to clean water is required to maintain hygiene behavior